Augmented glioma-targeted theranostics using multifunctional polymer-coated carbon nanodots. (October 2017) - Wang, Shanshan; Li, Chengyi; Qian, Min; Jiang, Huiling; Shi, Wei; Chen, Jian; Lächelt, Ulrich; Wagner, Ernst; Lu, Weiyue; Wang, Yi; Huang, Rongqin
Abstract: Overcoming biological barriers to imaging-guided site-specific delivery of therapeutics is the goal of current nanomedicine designs. Here, multifunctional polymer-coated carbon nanodots with an interleukin-6 (IL-6) fragment peptide for receptor-targeting (pCDPI) were prepared for drug delivery. The pCDPI exhibits small hydrodynamic diameters, high water solubility and biocompatibility. In vitro and in vivo results demonstrated that pCDPI can overcome the blood-brain barrier (BBB) and deeply penetrate into orthotopic glioma in mice, to inhibit IL-6-induced cell proliferation and achieve imaging-guided targeted drug delivery. Simultaneously, a pH-sensitive sustained release of doxorubicin (DOX) accompanied with real-time fluorescence monitoring was realized. A distinct synergistic therapeutic outcome could be achieved which suggests the presented nanomedicine having promising potential for future cancer treatments.